Few-layer MoS2 nanosheets anchored by CNT network for superior lithium storage. (20th January 2020) - Zheng, Yuhuan; Zheng, Xuan; Liu, Bin; Fu, Chenyang; Zhou, Liang; Liu, Yan; Wu, Wenwen; Xiong, Chuanxi; Liu, Zhikang; Yang, Quanling
Abstract: A novel self-assembled porous network of carbon nanotubes (CNTs) attached to molybdenum disulfide (MoS2 ) nanosheets is prepared via a one-step atmospheric pressure chemical vapor deposition (APCVD) method. The conventional APCVD method cannot be used to uniformly deposit three-dimensional (3D) structures. Instead, an alternative method is used to overcome the disadvantage of conventional APCVD, whereby molybdenum oxide (MoO3 ) is decomposed by a molybdate ion (MoO4 2− ) using in situ sulfuration. The synergy between the highly conductive CNT network and the layered MoS2 nanosheets contributes to the formation of high-efficiency ion/electron channels and improves the electrode durability and stability. The as-prepared C-MoS2 /CNT composite exhibits both high rate stability and long-term capacity in lithium-ion batteries (LIBs). The C-MoS2 /CNT electrode has a much higher initial discharge capacity of 1430 mAh g −1 at 100 mA g −1 and an impressive rate capability (885 mAh g −1 at 4000 mA g −1 ). Moreover, the C-MoS2 /CNT composite also exhibits a long cycle life of 1260 mAh g −1 after 200 cycles at 500 mA g −1 and 1066 mAh g −1 at 1000 mA g −1 after 250 cycles. The mechanism and design strategy presented in this work may provide ideas for the development of other electrode materials. Graphical abstract: Image 1 Highlights: An ultrastable and porous network of CNTs provides a fast channel for ions/electrons. The self-assembly and APCVD method uniformly disperses the MoS2 nanosheets in the C-MoS2 /CNT composite. Ultrathin MoS2 nanosheets are tightly deposited in situ onto the network of CNTs. The C-MoS2 /CNT electrode has good lithium storage performance.